Latencies of conditioned vocal responses to hearing test tones in killer whales (Orcinus orca) - Stephens, Jared; Accomando, Alyssa W.; Nease, Kayla; Branstetter, Brian K.; Robeck, Todd R. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionPerceived loudness is challenging to study in non-human animals. However, reaction time to an acoustic stimulus is a useful behavioral proxy for the assessment of perceived loudness. Understanding the effect of sound frequency and level on perceived loudness would improve prediction and modeling of anthropogenic noise impacts on marine mammals.MethodsIn this study, behavioral hearing tests conducted with two killer whales were analyzed to capture conditioned vocal response latency, which is the time between the onset of the acoustic signal and the onset of the response (i.e., reaction time).ResultsThe results showed that vocal reaction times decreased with increasing sensation level (i.e., sound pressure level above the baseline hearing threshold), while the effect of frequency on reaction time varied between the subjects. Reaction time as a function of sound duration is described, and equal-latency contours are presented.DiscussionThe data suggest that vocal reaction time decreases with increasing sensation level, therefore supporting the use of reaction time as a proxy for loudness perception in killer whales.